If the point Q = ( a , b , c ) is the reflection of the point P = ( − 6 , 2 , 3 ) about the plane 3 x − 4 y + 5 z − 9 = 0 , determine the value of a + b + c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Alternative method that doesn't intersect a line with the plane.
δ ( P , plane ) = 3 2 + ( − 4 ) 2 + 5 2 ∣ ∣ 3 ⋅ ( − 6 ) − 4 ⋅ 2 + 5 ⋅ 3 − 9 ∣ ∣ = 2 2 . We want to move twice this distance along the vector that is perpendicular to the plane n = ⎝ ⎛ 3 − 4 5 ⎠ ⎞ , that is P Q = ± 5 2 2 ⋅ 2 2 ⎝ ⎛ 3 − 4 5 ⎠ ⎞ = ± ⎝ ⎛ 5 1 2 5 − 1 6 4 ⎠ ⎞ .
That give two possibilities for Q : Q 1 ( 5 − 1 8 , 5 − 6 , 7 ) and Q 2 ( 5 − 4 2 , 5 2 6 , − 1 ) . To find the correct one, we find the middles M 1 and M 2 of P Q 1 and P Q 2 and see which one is on the plane.
M 1 ( 5 − 2 4 , 5 2 , 5 ) is on the plane, so the answer is Q = Q 1 . ( M 2 ( 5 − 3 6 , 5 1 8 , 1 ) is not on the plane.)
Hi teacher! I used another which seemed to be right, but it led to wrong answer. I don't know why. May you help me point out my mistake?
Call midpoint M (x,y,z) . So vector PM = (x + 6; y-2; z-3) which is parallel to normal vector (3,-4,5).
=> (x + 6; y-2; z-3) x (3,-4,5) = vector c = 0
=> 3z - 5x - 39 = 0 <=> z = (5x + 39) /3
-4x + 3y - 30 = 0 <=> y = (4x + 30) /3
Then put those x,y,z into equation of plane to determine M. We have P, midpoint M => Q.
Log in to reply
It's not ( x + 6 ) ⋅ ( − 4 ) + ( y − 2 ) ⋅ 3 = 0 but ( x + 6 ) ⋅ ( − 4 ) − ( y − 2 ) ⋅ 3 = 0 , which gives 4 x + 3 y + 1 8 = 0 and not − 4 x + 3 y − 3 0 = 0 .
If you don't have the same answer and don't know where's your mistake, just plug the values of the right answer in your equations. The problem will be where the equation is not satisfied.
Problem Loading...
Note Loading...
Set Loading...
First, we construct the line passing through ( − 6 , 2 , 3 ) that is perpendicular to the given plane. Since the normal vector to the plane is ⟨ 3 , − 4 , 5 ⟩ , we have that this line is
x y z = 3 t − 6 = − 4 t + 2 = 5 t + 3
Next, we'll plug this equation into the equation of the plane to find the point of intersection:
3 ( 3 t − 6 ) − 4 ( − 4 t + 2 ) + 5 ( 5 t + 3 ) − 9 = 0 ⟶ t = 5 2
Plugging this value of t back into the equation of the line yields the point ( − 5 2 4 , 5 2 , 5 ) . The vector from this point to P is ⟨ − 5 6 , 5 8 , − 2 ⟩ . So we negate this vector and add it to the point ( − 5 2 4 , 5 2 , 5 ) to get the reflected point.
⟨ 5 6 , − 5 8 , 2 ⟩ + ( − 5 2 4 , 5 2 , 5 ) = ( − 5 1 8 , − 5 6 , 7 )
Adding the x -, y -, and z -coordinates gives 5 1 1 = 2 . 2